2017
DOI: 10.1016/j.clbc.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Metaplastic Carcinoma of the Breast Is More Aggressive Than Triple-negative Breast Cancer: A Study From a Single Institution and Review of Literature

Abstract: We aimed to describe our experience with metaplastic breast carcinoma (MBC), evaluate its clinical outcome compared with triple negative breast cancer (TNBC), and provide a through and comprehensive review of the literature to date. We reviewed MBC cases (n=46) from our institution. The following variables were recorded, tumor histologic subtype, Nottingham grade, tumor size, lymph node status, TNM-stage, biomarkers profile, patient’s age and race, therapy modality (chemotherapy and radiation), and survival [d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
115
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(135 citation statements)
references
References 16 publications
(62 reference statements)
15
115
1
4
Order By: Relevance
“…TNBC tends to have a worse prognosis than other types of BC, [20][21][22][23] and the notion that metaplastic BC is more aggressive than TNBC has been corroborated by multiple smaller, retrospective investigations. [4,8,9,24] Such studies have shown similar patterns of diagnosis at advanced stages for metaplastic BC versus TNBC, owing to higher rates of cT3-4 disease rather than nodal involvement, [9,24] and in a single-institution review of 46 cases of metaplastic BC, patients with metaplastic BC had a significantly higher risk of local disease recurrence (30% vs. 15%; P=0.004). These features ultimately correlated with inferior 5-year disease-free survival rates (30% vs. 90%; P<0.001) and OS rates (65% vs. 87%; P=0.002) for patients with metaplastic BC relative to TNBC.…”
Section: Discussionmentioning
confidence: 96%
“…TNBC tends to have a worse prognosis than other types of BC, [20][21][22][23] and the notion that metaplastic BC is more aggressive than TNBC has been corroborated by multiple smaller, retrospective investigations. [4,8,9,24] Such studies have shown similar patterns of diagnosis at advanced stages for metaplastic BC versus TNBC, owing to higher rates of cT3-4 disease rather than nodal involvement, [9,24] and in a single-institution review of 46 cases of metaplastic BC, patients with metaplastic BC had a significantly higher risk of local disease recurrence (30% vs. 15%; P=0.004). These features ultimately correlated with inferior 5-year disease-free survival rates (30% vs. 90%; P<0.001) and OS rates (65% vs. 87%; P=0.002) for patients with metaplastic BC relative to TNBC.…”
Section: Discussionmentioning
confidence: 96%
“…Such results are similar to our multivariate analysis that showed no significant difference in OS and DDFS between the two cohorts. However, other investigations have demonstrated unfavorable results for patients with MBC compared to those with TNBC or hormone receptor-negative IC-NST [6,[36][37][38]. The varying results highlight the need for additional larger retrospective studies to understand the biology and best treatment practices to treat patients with MBC.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, only a few reports have attempted to investigate the differential prognosis and predictive factors that make MBC different from more common types of malignant breast cancer 17–20. For example, a study by El Zein et al including 46 cases of MBC showed that metaplastic breast cancer presented at a more advanced stage than TNBC and was more likely to recur, indicating MBC was clinically more aggressive than TNBC 20. Jung et al reported a study containing 35 patients with MBC and 2839 with IDC, and showed that patients with MBC presented with larger tumour size, more distant metastasis at the first diagnosis, higher histological grade and poorer prognosis 18.…”
Section: Introductionmentioning
confidence: 99%